2018
DOI: 10.1038/s41467-018-04444-w
|View full text |Cite
|
Sign up to set email alerts
|

Male germ cells support long-term propagation of Zika virus

Abstract: Evidence of male-to-female sexual transmission of Zika virus (ZIKV) and viral RNA in semen and sperm months after infection supports a potential role for testicular cells in ZIKV propagation. Here, we demonstrate that germ cells (GCs) are most susceptible to ZIKV. We found that only GCs infected by ZIKV, but not those infected by dengue virus and yellow fever virus, produce high levels of infectious virus. This observation coincides with decreased expression of interferon-stimulated gene Ifi44l in ZIKV-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 48 publications
(40 reference statements)
1
70
1
1
Order By: Relevance
“…This cellular physiology and ZIKV modulation can develop an important factor that may lead to the establishment of viruses in this organ. Other cell types in the testicle can support the ZIKV infection, such as testicular fibroblast, germ cells, and spermatocyte [43,83]. The TAM receptor, AXL, promotes the ZIKV entrance in SCs and contributes negatively to the antiviral states of SCs [82].…”
Section: Zikv On Male Reproductive Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…This cellular physiology and ZIKV modulation can develop an important factor that may lead to the establishment of viruses in this organ. Other cell types in the testicle can support the ZIKV infection, such as testicular fibroblast, germ cells, and spermatocyte [43,83]. The TAM receptor, AXL, promotes the ZIKV entrance in SCs and contributes negatively to the antiviral states of SCs [82].…”
Section: Zikv On Male Reproductive Tractmentioning
confidence: 99%
“…Microorganisms coming from blood or urogenital infections enter into a testicular environment and disrupt tissue homeostasis, leading to activation of local immune system [3]. This process triggers testicular inflammation and may alter tissue metabolism, signalization, cellular function, and leading to impaired spermatogenesis and spermiogenesis [42,43]. Many pathogens have been shown to cause male infertility by many mechanisms, induced inflammation being the key for most of them.…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular viral persistence is likely an important component for long-term sexual transmission. Although the cells that act as reservoirs of ZIKV in testes and the reproductive tract are unknown, possible reservoirs in the host are SC [67,68] germ cells [69], Leydig cells [70] and epididymal epithelial cells [59,62] which have been shown to support persistent infections of ZIKV (Figure 1). When primary SCs persistently infected with two strains of ZIKV (PRVABC59 or MR766) were monitored for a period of 6 weeks, it was found that 15% of the cells were still positive for both strains of ZIKV [67].…”
Section: Persistence and Tropism Of Zikv On The Male Reproductive Tractmentioning
confidence: 99%
“…LSM14A, a host restriction factor required for viral sensing and interferon induction was the most downregulated transcript in the ZIKV infected cells . Immune‐staining studies on human testicular tissue biopsy samples exposed to ZIKV indicated that human germ cells supported viral replication . ZIKV infection of cells of testis can affect the architecture of the organ.…”
Section: Pathophysiologymentioning
confidence: 99%